2014
DOI: 10.1186/2046-2395-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of Caenorhabditis elegansFOXO/DAF-16 modulates lifespan

Abstract: BackgroundInsulin/IGF-1 signaling plays a central role in longevity across phylogeny. In C. elegans, the forkhead box O (FOXO) transcription factor, DAF-16, is the primary target of insulin/IGF-1 signaling, and multiple isoforms of DAF-16 (a, b, and d/f) modulate lifespan, metabolism, dauer formation, and stress resistance. Thus far, across phylogeny modulation of mammalian FOXOs and DAF-16 have focused on post-translational regulation with little focus on transcriptional regulation. In C. elegans, we have pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 81 publications
(118 reference statements)
6
44
4
Order By: Relevance
“…Both miR-34 and daf-16 expression levels were shown to be increased upon dauer formation2658 and also in adults in an age-dependent manner5960, suggesting a link between these regulators of gene expression. By engineering promoter truncations we showed that an IRE sequence, which binds DAF-16, is present in mir-34 promoter.…”
Section: Discussionmentioning
confidence: 98%
“…Both miR-34 and daf-16 expression levels were shown to be increased upon dauer formation2658 and also in adults in an age-dependent manner5960, suggesting a link between these regulators of gene expression. By engineering promoter truncations we showed that an IRE sequence, which binds DAF-16, is present in mir-34 promoter.…”
Section: Discussionmentioning
confidence: 98%
“…We examined the mechanism by which HEL-1 influenced the expression of DAF-16 target genes by assessing known modes of activation, including physical interaction with cofactors (20), nuclear translocation (24)(25)(26), and induction at the transcriptional level (27). We performed coimmunoprecipitation assays in cultured mammalian cells and found that HEL-1 bound to DAF-16 ( Fig.…”
Section: Hel-1 Extends Lifespan By the Induction Of Daf-16/foxo-depenmentioning
confidence: 99%
“…C. elegans with partial loss-of-function mutations in daf-2 , the C. elegans insulin/IGF-1-receptor gene, not only live longer but also maintain more youthful characteristics, such as active movement (Huang et al, 2004; Kenyon et al, 1993), neuronal function (Liu et al, 2013) and memory (Kauffman et al, 2010), indicating an extension of healthspan as well as lifespan. However, a recent study followed functional ability of daf-2 mutants and found that the daf-2 healthspan, though chronologically longer than that of wild type, did not scale with lifespan, resulting in a disproportionately extended period of age-related decrepitude (Bansal et al, 2014). This report was disconcerting because such an outcome would be undesirable in a human society, where population aging has already massively increased healthcare costs (Centers for Medicare & Medicaid Services, 2015; Meara et al, 2004), and also brought into question the validity of C. elegans as a model organism to study healthy life extension.…”
Section: Introductionmentioning
confidence: 99%